Occurrence of fungal foliar diseases of tomato in different agro-ecological zones of Kirinyaga County, Kenya - Fredrick Otieno Ogolla; Moses M Muraya; Benson O Onyango (Fundamental and Applied Agriculture, 2022)
Tomato production is characterized by inconsistent quality and yields due to biotic constraints such as fungal foliar diseases. Information on the occurrence of the diseases in different agro-ecological zones of Kenya is scanty. This study assessed the occurrence of early blight, late blight and Septoria spot diseases in tomato farms in five agro-ecological zones (AEZ) of Kirinyaga County in Kenya (UM2, UM3, UM4, LM3 and LM4) using cross sectional survey method. Macro plots were systematically established diagonally in tomato farms and were used to assess disease incidence and severity. Incidences and severity data were subjected to analysis of variance (ANOVA) using Krukal wallis H test at α = 0.05. Median comparison was performed using Steel Dwass Critchlow Fligner with bonferroni adjustment in Statistical Analysis System (SAS) version 9.4. Incidences and severity of early blight, late blight and Septoria spot in tomato farms were significantly different (p< 0.05) among the villages and agro-ecological zones. Incidence of early blight ranged from 35.7% to 76.65% with severity ranging from 17.15% to 50.87%. The incidence of Septoria spot ranged from 23.56% to 93.42% with severity ranging from 16.67% to 44.44%. The incidence of late blight ranged from 33.33% to 86.63% with severity ranging from 16.67% to 33.33%. The incidence of early blight was significantly higher in AEZ UM3 (Median= 75%), the incidence of Septoria spot was significantly higher in AEZ LM4 (Median = 83.33%) while the incidence of late blight was significantly higher in AEZ UM3 (Median= 50%). The severity of early blight was significantly higher in AEZ UM3 (Median = 38.89%), Septoria spot was significantly severe in AEZ LM4 (Median = 40.28%) while severity of late blight was significantly higher in AEZ UM4 (Median= 32.72%). It can be concluded that the incidences and severity of the three foliar fungal diseases of tomato differed in different AEZ of Kirinyaga County. These findings serve as a baseline study and can be used to enlighten farmers on tomato fungal diseases in the area. However, there is a need for studies to evaluate predisposing factors and to determine the economic impact of foliar fungal diseases of tomatoes in Kirinyaga County. [Fundam Appl Agric 2022; 7(1.000): 31-46]